Organic Matrix in Reverse Osmosis Concentrate: Composition and Treatment Alternatives - Cemre Birben, Nazmiye; Senem Uyguner-Demirel, Ceyda; Bekbolet, Miray (Current Organic Chemistry, 2017)
Being regarded as one of the critical components of water recycling programs, membrane treatment in particular reverse osmosis process has gained special interest. Although reduced cost of membrane modules caused an increase in the application, a major challenge has come up with the generation of reverse osmosis concentrate. The major concern of reverse osmosis concentrate is that it contains almost all the constituents 6-7 times more concentrated than the reverse osmosis feed. Therefore, treatment of toxic and/or bio-accumulative contaminants of reverse osmosis concentrates to an appropriate level has become a crucial topic. This paper aimed to review organic constituents of municipal reverse osmosis concentrate (ROCm) in terms of their characteristics and their treatment by physicochemical and advanced oxidation processes. It could be concluded that the application of advanced oxidation processes either alone or in combination with pretreatment processes could be regarded as promising technologies on the removal of organic constituents of ROCm. On the other hand, these technologies should be cautiously assessed from different perspectives, such as energy efficiency, operational parameters, combination with other technologies and potential hazard risk to the environment in terms of toxicity.
Keywords: organic matrix